Cocconeis kurakakea, a new diatom species from Nukutavake (Tuamotu Archipelago, South Pacific): description and comparison with C. diruptoides and C. pseudodiruptoides - Riaux-Gobin, Catherine; Witkowski, Andrzej; Jordan, Richard W.; Parravicini, Valeriano; Planes, Serge (Phytotaxa, 2018)
During the ‘Tara Pacific 2016–2018 Expedition’, marine benthic diatom samples were collected from several Tuamotu atolls in the South Pacific. Preparation and examination of these samples were conducted following standard methods including light and scanning electron microscopy. A small-celled taxon from the genus Cocconeis Ehrenb. (Bacillariophyceae) is described from the Nukutavake reef, and compared to several other taxa for which the definition is not always clear (e.g., Cocconeis diruptoides Hust. and Cocconeis pseudodiruptoides Foged). The new taxon is present only on one of the investigated Tuamotu atolls, possibly indicating local endemism.